Process improvement framework for emerging information technology organizations - Varma, Praveen G. (2007)
A process model is a tool that measures progress, maintains processes and implements improvement within information technology organizations. Capability Maturity Model Integration (CMMI) is one such model-based process approach that addresses process-orientation needs. However, such models are usually considered when the IT companies are well established and their operations are wide-spread. It is necessary to bridge the widening gaps between the growing organizations and those that are established where their processes are well defined under high process standards. The cause of research for this thesis will be toward applying basic process-oriented methodologies and measures to emerging IT organizations that would further be mapped toward CMMI standardizations. This would help such companies reach to a level where process standardizations could be implemented and managed. Most knowledge needed for this research was gathered from SCAMPI [5], OWPL [3], Carnegie Mellon Software Engineering Institute's proposed models, and CMMI registered literatures [1], [20], [15]. This project was based on the experiences and research done on one such growing information technology organization which is considering model based process approach. The project developed a framework for emerging Information Technology organizations by mapping the OWPL model to CMMI practices and further developing detailed instruments for conducting process appraisal in SME's (Small and Medium sized Enterprises). A process guideline that contributes to process-oriented development was built as a result of this project.